Collaborating 4Cs framework model and case study-based learning for enhancing language competence - Belinda Marie Balraj, Enock Amalanathan, (Opción, 2019)
This paper is a preliminary report on the outcomes of a CLIL (Content and language integrated learning) program interwoven with case study-based learning carried out during an EAP (Employee assistance program) course in a military training center. The case study base learning is an active learning approach which facilitates resourceful contextual information and opportunities for learners. The study shows that upon completion of the CLIL program interwoven with Case study-based learning projects rewarding outcomes in terms of content acquisition, language skills and interdisciplinary competence. In conclusion, military training centres need to create an educational training system where language education is complement of each other.